The Effect Of Regional Levies On The Original Regional Revenue Of South Sulawesi Province (Case Study Of The Office Of The Regional Revenue Agency Of South Sulawesi Province) - Wisudawaty, Ika; Nurjannah, Nurjannah (International Journal of Education, Vocational and Social Science, 2024)
This study aims to determine the influence of regional levies on the original regional income of South Sulawesi Province. The variables of this study are: regional original revenue as a bound variable (Y) measured by regional taxes, regional levies, results of separated regional wealth management, and other legitimate PAD, and regional levies as independent variables (X) measured by public service levies, business service levies, and certain licensing levies. The population of this study is the South Sulawesi Provincial Budget Revenue Report, while the sample is 36 data on the realization of regional levies and local revenue of South Sulawesi Province for the period of 2022-2024 using a saturated sample. Data collection was carried out using documentation techniques. Data analysis was carried out by data normality test, simple linear regression test, and hypothesis test. The results of this study show that regional levies have a positive and significant effect on the original regional income of South Sulawesi Province.